Analysis of Readiness for Becoming Teacher Based on the Theory of Planned Behavior - Dyah Ayu Purwitasari; Slamet Fauzan (Universitas Negeri Semarang, 2025)
This research aims to identify the factors behind the readiness of accounting education students as prospective teacher. This study applies the Theory of Planned Behavior. Research population consists of Undergraduate Students of Accounting Education in State University of Malang on batch 2019-2022, totaling 251 students. From those population, 155 students are chosen to use slovin technique to determine measurement of sample. To make sure the proportional representative of every batch, proportionate stratified random sampling method was applied in taking sampling. The questionnaire is used as data collecting technique which is analyzed by using Structural Equation Modeling Smart PLS 3. It was found in this study that family environtment and self-efficacy in teaching directly influence to the interest. Meanwhile, the perception of teacher profession does not significally affect to the interest. Family environtment and self-afficacy in teaching increase personal the readiness to be a teacher. Eventhough the perception of teacher profession does not influence the teaching readiness, but the readiness of teaching is influenced by interest. Interest is proven to mediate the influence of family environment on teaching readiness. In addition, interest also successfully mediate the influence of teaching self-efficacy on teaching readiness. However, interest does not play a strong enough role as an intervening variable in the relationship between perception of the teaching profession and teaching readiness. The benefit of this study is to provide input to higher education institutions as a basis for conducting more in-depth curriculum evaluations.